2021
DOI: 10.1523/jneurosci.3180-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of phosphodiesterase 7 enzymes reduces motivation for nicotine use through modulation of mesolimbic dopaminergic transmission

Abstract: Selective inhibition of phosphodiesterase 7 enzymes reduces motivation for nicotine use through modulation of mesolimbic dopaminergic transmission

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Electrophysiological studies support synaptic potentiation of nAc excitatory synapses where prolonged abstinence following cocaine, enhances AMPAR-dependent synaptic strength with both increases in mEPSC amplitude and AMPA/NMDA ratio ( Kourrich et al, 2007 ; Ortinski et al, 2012 ). Our findings suggest a possibly common AMPAR nAcS metaplasticity during forced abstinence for both nicotine and cocaine beyond the other evidences of shared molecular effects within the accumbens of these two drugs of abuse ( Di Chiara and Imperato, 1988 ; Pich et al, 1997 ; McClung et al, 2004 ; Ciccocioppo et al, 2021 ). Importantly negative affective states, generally experienced during late nicotine withdrawal, are characterized by increased AMPA receptor expression in nAcS selectively in dopamine D1 MSNs ( Pignatelli et al, 2021 ) In addition, cocaine abstinence has been shown to selectively increase the rectification of AMPA receptor-mediated currents in nAcS dopamine D1 receptor expressing MSNs ( Inbar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 57%
“…Electrophysiological studies support synaptic potentiation of nAc excitatory synapses where prolonged abstinence following cocaine, enhances AMPAR-dependent synaptic strength with both increases in mEPSC amplitude and AMPA/NMDA ratio ( Kourrich et al, 2007 ; Ortinski et al, 2012 ). Our findings suggest a possibly common AMPAR nAcS metaplasticity during forced abstinence for both nicotine and cocaine beyond the other evidences of shared molecular effects within the accumbens of these two drugs of abuse ( Di Chiara and Imperato, 1988 ; Pich et al, 1997 ; McClung et al, 2004 ; Ciccocioppo et al, 2021 ). Importantly negative affective states, generally experienced during late nicotine withdrawal, are characterized by increased AMPA receptor expression in nAcS selectively in dopamine D1 MSNs ( Pignatelli et al, 2021 ) In addition, cocaine abstinence has been shown to selectively increase the rectification of AMPA receptor-mediated currents in nAcS dopamine D1 receptor expressing MSNs ( Inbar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 57%
“…4.2.5. Phosphodiesterase 7 PDE7 is another isoenzyme with specific affinity for cAMP, as shown by the effect of selective inhibitors significantly elevating cAMP levels in the CNS [163]. PDE7 has two known isoforms, PDE7A and PDE7B, each with distinct tissue distribution and subcellular localization.…”
Section: Phosphodiesterasementioning
confidence: 99%